Sequence Matching Analysis for Curriculum Development - Liem Yenny Bendatu; Bernardo Nugroho Yahya (Institute of Research and Community Outreach - Petra Christian University, 2015)
Many organizations apply information technologies to support their business processes. Using the information technologies, the actual events are recorded and utilized to conform with predefined model. Conformance checking is an approach to measure the fitness and appropriateness between process model and actual events. However, when there are multiple events with the same timestamp, the traditional approach unfit to result such measures. This study attempts to develop a sequence matching analysis. Considering conformance checking as the basis of this approach, this proposed approach utilizes the current control flow technique in process mining domain. A case study in the field of educational process has been conducted. This study also proposes a curriculum analysis framework to test the proposed approach. By considering the learning sequence of students, it results some measurements for curriculum development. Finally, the result of the proposed approach has been verified by relevant instructors for further development.